Successful lifestyle modification in older patients with coronary artery disease: results from the RESPONSE-2 trial. (25th November 2020) - Jepma, P; Jorstad, H.T; Snaterse, M; Ter Riet, G; Kragten, J.A; Lachman, S; Minneboo, M; Boekholdt, S.M; Peters, R.J.G; Scholte Op Reimer, W.J.M
Abstract: Introduction: Interventions to reduce lifestyle-related risk factors (LRFs) such as overweight, physical inactivity and smoking are effective in the secondary prevention of cardiovascular events. However, evidence of the effects of lifestyle-related secondary prevention programmes in older patients with coronary artery disease (CAD) is less conclusive than in younger patients. Purpose: To compare the treatment effect on lifestyle-related risk factors (LRFs) in older (≥65 years) versus younger (<65 years) patients with CAD in The Randomised Evaluation of Secondary Prevention by Outpatient Nurse SpEcialists 2 (RESPONSE-2) trial. Methods: The RESPONSE-2 trial was a community-based lifestyle intervention trial (N=824) comparing nurse-coordinated referral to a comprehensive set of three lifestyle interventions (physical activity, weight reduction and/or smoking cessation) to care as usual. The primary outcome was the proportion of patients with improvement at 12 months follow-up (N=711) in at least 1 LRF (without deterioration in the other LRFs). In the current analysis, we assessed if the overall beneficial treatment effect of the RESPONSE-2 intervention varied by age. Results: At baseline, older patients (n=245, 69.2±3.9) had significantly more serious cardiovascular risk profiles and comorbidities (hypertension, diabetes mellitus and peripheral artery disease) than younger patients (n=579, 53.7±3.9). The overall treatment effect did not vary by age (OR overall 1.67, 95% CI 1.22 - 2.31). However, older patients were more likely to achieve ≥5% weight loss (OR old 5.58, 95% CI 2.77–11.26 vs. OR young 1.57, 95% CI 0.98 - 2.49, P interaction=0.003) and younger patients were more likely to show non-improved individual LRFs (OR old 0.38, 95% CI 0.22–0.67 vs. OR young 0.88, 95% CI 0.61–1.26, P interaction=0.01). Conclusion: Despite more serious cardiovascular risk profiles and comorbidities among older patients, nurse-coordinated referral to community-based lifestyle interventions was at least as successful in improving LRFs in older as in younger patients. Higher age alone should not be a reason to withhold lifestyle interventions in patients with CAD. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The RESPONSE-2 trial was sponsored by Weight Watchers International, Inc. (New York, New York) and Philips Consumer Lifestyle (the Netherlands). This work was also supported by the Netherlands Organisation for Scientific Research (NWO) to PJ.